PERAN GANDA PEREMPUAN BURUH TANI UNTUK MENUNJANG PEREKONOMIAN KELUARGA: PERAN GANDA PEREMPUAN BURUH TANI UNTUK MENUNJANG PEREKONOMIAN KELUARGA - Siti (Universitas Sarjanawiyata Tamansiswa, 2024)
The increase in the number of married women actively participating in the workforceis a clear indicator of the increasing economic participation of their partners. As aresult of their efforts to support their families, gender approaches to collaboration inall areas of life have been strengthened; Therefore, the role of women has evolvedrapidly in recent times. However, women's progress has not changed their traditionalfunction in the home or their role as contributors to the economy. This study tries tounderstand the causes that enable women to take on various roles and what impactsoccur if women play multiple roles in the family. Descriptive qualitative methods areused here. Snowball sampling was used to select sources. Data collection methodsinclude detailed recording and conducting interviews, which are then analyzedincluding data reduction, data presentation, and data verification. These findingsshow that 1) economic, environmental, and educational problems are the root causesof women doing many tasks, and 2) women's participation in multiple roles haspositive and negative impacts. There will be a positive impact on family finances andreligious practices. Meanwhile, the negative impact is the emergence of stress due tohaving to carry a double burden, fatigue and depression, constant worry, and disputeswith one's partner.